2022
DOI: 10.5713/ab.21.0113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different nitrogen doses and cultivars on fermentation quality and nutritive value of Italian ryegrass (Lolium multiflorum Lam.) silages

Abstract: Title of the manuscript: Effects of different nitrogen doses and cultivars on fermentation quality and nutritive value of Italian ryegrass (Lolium multiflorum Lam.) silages ABSTRACT Objective: The fermentation profile and silage quality of 3 Italian ryegrass (Lolium multiflorum Lam.) (Devis, Hellen and Trinova) cultivars (cvs. Devis, Hellen and Trinova) treated with 5 nitrogen doses (0, 50, 100, 150 and 200 kg ha -1 ) were evaluated. Methods: The experiment was laid out in split plot in randomized completed bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
7
15
0
Order By: Relevance
“…Furthermore, lower contents of DM and WSC led to more protein degradation during ensiling of Italian ryegrass (Guo et al, 2014). The silage had higher NH 3 -N and lactic acid contents, which was related to the metabolic activities of plant proteases and lactic acid bacteria, and some studies had also found a similar tendency (Ertekin et al, 2022). On the other hand, the DM content of the second cut was higher than that of the first cut (p < .001).…”
Section: Silage Fermentation Qualitymentioning
confidence: 81%
“…Furthermore, lower contents of DM and WSC led to more protein degradation during ensiling of Italian ryegrass (Guo et al, 2014). The silage had higher NH 3 -N and lactic acid contents, which was related to the metabolic activities of plant proteases and lactic acid bacteria, and some studies had also found a similar tendency (Ertekin et al, 2022). On the other hand, the DM content of the second cut was higher than that of the first cut (p < .001).…”
Section: Silage Fermentation Qualitymentioning
confidence: 81%
“…While some forb species may limit the preparation of high‐quality silage when present in large proportions or harvested at an advanced stage of maturity (e.g., Heracleum sphondylium L.), other forbs such as Anthriscus sylvestris (L.) Hoffm., Ranunculus acris L., Ranunculus repens L. or Taraxacum officinale aggr ., are characterized by a comparable ensilibility as ryegrasses (Wyss & Vogel, 1999). However, the silage quality of forage from species‐rich grasslands is often inferior to silage prepared from intensively managed swards based on grass‐ or legume species (Ertekin et al, 2022; Ineichen et al, 2019; Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable climatic conditions are also one of the most important factors to reach the desired yield (Ertekin et al, 2019;Ertekin et al, 2022) and fiber quality in cultivars (Van Esbroeck and Bowman, 1998). Although there is a very strong cotton production structure in our country, there are many problems that can negatively affect this strong structure.…”
Section: Introductionmentioning
confidence: 99%